Enhancing SDGs in Barito Kuala: Enterprise Architecture for Smart Village Development using TOGAF ADM 9.2 in Sungai Pitung - Yazid Aufar; Tesdiq Prigel Kaloka; Marhusin Marhusin; Muhammad Aditia; Salmah Salmah; M. Junaidi (Universitas Islam Indragiri, 2026)
Sustainable village development is essential for realizing the Sustainable Development Goals (SDGs), specifically regarding poverty eradication (SDG 1), inequality reduction (SDG 10), and the establishment of sustainable communities (SDG 11). This study formulates a smart village framework for Sungai Pitung Village, Barito Kuala, by utilizing the Village Information System (SID) to enhance local governance and economic conditions. The methodology employs TOGAF ADM 9.2, covering the Preliminary phase, Architecture Vision, Business Architecture, Information Systems Architecture, and Technology Architecture. The novelty of this research lies in the strategic integration of Village Development Index (IDM) indicators and Village SDGs (Ministerial Regulation No. 13 of 2020) directly into the architectural blueprints. This approach ensures that the resulting digital roadmap is legally and contextually compliant with Indonesian rural mandates. The framework is validated through a formal evaluation of research results with relevant stakeholders to ensure it addresses the digital divide and operational inefficiencies. The findings provide a holistic IT architecture that standardizes technology catalogs and aligns village services with national development targets, ultimately fostering an enhanced quality of life for rural inhabitants.